2016
DOI: 10.15640/jehd.v5n1a25
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Social Studies Teachers’ Competence in the Use of Playway Method in Lower Primary Schools in Osun State, Nigeria

Abstract: The study assessed Social Studies teachers' competence in the use of playway method in lower primary Social Studies classroom in Osun State, Nigeria. It examined their knowledge, competence and factors that might influence their competence in the use of playway method in Social Studies classroom. The study adopted qualitative descriptive research design. Nursery and Primary school teachers in Osun State constituted the population for the study. One hundred and fifty-six (156) teachers were sampled using strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Also, Suratman et al (2020) showed that teacher certification positively affects teaching quality, referring to both academic and professional certifications, while certification has been identified as the primary factor in determining whether a teacher is qualified to teach (Sindelar et al, 2019). Furthermore, some other studies pointed out that teachers' qualifications have significant influences on their teaching quality (Lee & Mamerow, 2019;Adeyemi, 2020;Yusuf, 2020). Additionally, students who were taught by multiple highly qualified instructors were more likely to earn advanced degrees (Betts et al, 2003;Lee & lee, 2020).…”
Section: Graduation Placementioning
confidence: 99%
“…Also, Suratman et al (2020) showed that teacher certification positively affects teaching quality, referring to both academic and professional certifications, while certification has been identified as the primary factor in determining whether a teacher is qualified to teach (Sindelar et al, 2019). Furthermore, some other studies pointed out that teachers' qualifications have significant influences on their teaching quality (Lee & Mamerow, 2019;Adeyemi, 2020;Yusuf, 2020). Additionally, students who were taught by multiple highly qualified instructors were more likely to earn advanced degrees (Betts et al, 2003;Lee & lee, 2020).…”
Section: Graduation Placementioning
confidence: 99%
“…Nevertheless, lectures, textbooks, and assignments appear to dominate instruction without motivating students to learn. Studies show that when a diversity of teaching approaches are used, students are more interested in the subject (Adeyemi, 2016;Huck, 2019;Malik, 2018;Namamba & Rao, 2017).…”
Section: Understanding Teachers' Ability To Deliver Social Studies Co...mentioning
confidence: 99%
“…Self-directed teaching and learning entail engaging students in learning activities that allow them to use their imagination and intuition (Nzima, 2016;Poznanski et al, 2018;Prasetya et al, 2020). As a result, self-directed learning has the potential to improve optimal interaction between and among Social Studies students, fostering effective decision-making when debating and analysing societal issues (Adeyemi, 2016;Meziobi & Meziobi, 2016).…”
Section: Understanding Teachers' Ability To Deliver Social Studies Co...mentioning
confidence: 99%
“…The domineering method of teaching renders learner passive in class. This is also of the view of Adeyemi (2016) that the play method of teaching that is advocated in the national policy on early childhood education is not efficiently used in most of the early childhood care centres, as most of the teachers are not trained on the use of it. Also, Nakpodia (2003) lamented that the basic challenge facing the implementation of the play-way method is that very few of early childhood education teachers are received for training in early childhood education.…”
Section: Page 84mentioning
confidence: 99%